Mucus Is a Key Factor in Neisseria meningitidis Commensalism - Melanie M. Callaghan; Joseph P. Dillard (mSphere, 2019)
The work presented by Audry et al. (M. Audry, C. Robbe-Masselot, J.-P. Barnier, B. Gachet, et al., mSphere 4:e00494-19, 2019, https://doi.org/10.1128/mSphere.00494-19 ) gives new insight into the interactions of Neisseria meningitidis and the human nasopharynx.